2021
DOI: 10.3892/mmr.2021.11849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renalase deficiency on liver fibrosis markers in a nonalcoholic steatohepatitis mouse model

Abstract: Progression of nonalcoholic steatohepatitis (NASH) is attributed to several factors, including inflammation and oxidative stress. In recent years, renalase has been reported to suppress oxidative stress, apoptosis and inflammation. A number of studies have suggested that renalase may be associated with protecting the liver from injury. The present study aimed to clarify the effects of renalase knockout (KO) in mice with NASH that were induced with a choline-deficient high-fat diet (CDAHFD) supplemented with 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…This suggests the possibility that if RNLS activates PMCA4b, NO accumulation could be reduced, leading to less severe injury or more rapid recovery. NF-κB-regulated RNLS expression has also been shown to cause increased phosphorylation of AKT through a PMCA4b-dependent mechanism [58]. In B16-F10 cells, PMCA4b was also found to have a key role in RNLS-dependent ERK and STAT3 phosphorylation [11].…”
Section: Rnls Stimulates Distinct Intracellular Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the possibility that if RNLS activates PMCA4b, NO accumulation could be reduced, leading to less severe injury or more rapid recovery. NF-κB-regulated RNLS expression has also been shown to cause increased phosphorylation of AKT through a PMCA4b-dependent mechanism [58]. In B16-F10 cells, PMCA4b was also found to have a key role in RNLS-dependent ERK and STAT3 phosphorylation [11].…”
Section: Rnls Stimulates Distinct Intracellular Signalsmentioning
confidence: 99%
“…It is suggested that this hepatocyte dysfunction and hepatic fibrosis progression could be connected to the absence of RNLS. Additionally, the absence of RNLS may cause an increase in oxidative stress and bring on macrophage infiltration in these tissues [58].…”
Section: Othersmentioning
confidence: 99%
“…A theoretically similar approach, by direct targeting of the molecular mechanisms that underlie EMT, has been suggested as a novel opportunity for an effective anti-fibrotic therapy ( 38 , 85 , 97 ). Finally, the related research of renalase’s effects on fibrosis markers in the liver-injury mouse model ( 19 ) further confirms that the lack of the renalase gene favors oxidative stress promotion, significant macrophage accumulation, as discussed, and increased TGF-β expression, finally emerging as liver fibrosis progression. A schematic view of the TGF-β-mediated activation of non-canonical pathways with respect to signaling arms that may be targeted by renalase is depicted in Figure 1 , and a summary of current experimental evidence is presented in Table 1 .…”
Section: The Identification Of Renalase As a Relevant Antifibrotic Mo...mentioning
confidence: 66%
“…Additional studies provided evidence that renalase’s distribution is spread far beyond the kidneys and heart. Therefore, its tissue expression pattern, to varying extents, is revealed in the liver ( 19 , 44 ), small intestines ( 45 ), skeletal muscles ( 46 ), pancreas ( 22 , 47 ), cornea ( 48 ), brain and peripheral nerves ( 49 , 50 ), and malignant tissue as well ( 22 , 23 , 51 ), implying renalase’s remote role in general homeostasis and its possible relevant biologic activity. Accordingly, the latest research indicates a potential role for renalase in placental development and function, owing to its expression in the placenta throughout human gestation ( 25 ).…”
Section: Renalase’s Structure Expression and Cell Biologymentioning
confidence: 99%
“…α-SMA expression in HSCs could also be lowered through overexpression of cytochrome P450 omega-hydroxylase 4a14 (CYP4A14) 95 or through knock-out of renalase (an oxidative stress suppressor) in NASH mice 96 . Inhibition of focal adhesion kinase reduced α-SMA and collagen overexpression in an animal model, in the presence of TGFβ 20 (Table 2).…”
Section: Cytoskeleton Protein In Nafld Diagnosismentioning
confidence: 99%